2007
DOI: 10.1186/1751-0147-49-21
|View full text |Cite
|
Sign up to set email alerts
|

A previously unidentified Chorioptes species infesting outer ear canals of moose (Alces alces): characterization of the mite and the pathology of infestation

Abstract: Background: During the past decade, Chorioptes mites occupying the outer ear canals have been a common finding at routine necropsies of moose (Alces alces) in Sweden, but neither the taxonomy of the mites nor lesions from the infestation have been investigated. In this study, the mites are characterized by morphological and molecular techniques, and the histopathology of the skin of the outer ear canal is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
3
17
0
Order By: Relevance
“…Histopathological analysis constitutes an important tool for diagnosing chorioptic mange, based on previous studies. The histopathological findings of this study were similar to those previously reported in case of Chorioptes infestations (HESTVIK et al, 2007). Consequently, since secondary bacterial infections were found in the integumentary system of cattle, in wounds induced by C. bovis, we concluded that this mite facilitated this type of secondary infection.…”
Section: Resultssupporting
confidence: 91%
“…Histopathological analysis constitutes an important tool for diagnosing chorioptic mange, based on previous studies. The histopathological findings of this study were similar to those previously reported in case of Chorioptes infestations (HESTVIK et al, 2007). Consequently, since secondary bacterial infections were found in the integumentary system of cattle, in wounds induced by C. bovis, we concluded that this mite facilitated this type of secondary infection.…”
Section: Resultssupporting
confidence: 91%
“…The protonymph and deutonymph stages of male and female mites were not differentiated in the Table 1. Comparative lengths of setae on adult male mites collected from the Holstein cattle in this study with those of male mites reported by Sweatman [3] and Hestvik et al [5] are provided in Table 2. All developmental stages of mites, from the egg to adult stages, were observed from samples collected from affected cattle (Fig.…”
Section: Case Recordmentioning
confidence: 85%
“…Although 3 additional Chorioptes spp., C. crewei Lavoipierre, 1958, C. mydaus Fain, 1975, and C. panda Fain and Leclerc, 1875, were described after Sweatman's revision in 1957, their validity is considered questionable, because features used for discriminating these taxons were not convincing and no transfer or cross-breeding studies were done [4]. Recently Hestvik et al [5] reported a previously unidentified Chorioptes species infesting the outer ear canals of the moose (Alces alces) which differ morphologically and genetically from other Chorioptes species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chorioptes spp. may cause skin lesions in the outer ear canal of moose (Hestvik et al, 2007) and have also been associated with single cases of generalized alopecia in moose in Norway and Sweden. Histologically, the ear skin lesions caused by this mite seem quite similar to those seen in our study.…”
Section: Discussionmentioning
confidence: 99%